Penerapan Nilai Spiritual Profil Pelajar Pancasila Dalam Pandangan Filsafat Perenialisme Thomas Aquinas - Saputra, Irwan; Sayekto, Giri; Fauziati, Endang (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research discusses the application of the spiritual values ​​and profile of Pancasila students in the educational context by referring to the philosophical views of perennialism, especially those inspired by the thoughts of Thomas Aquinas. The research was carried out using a literature study method related to Thomas Aquinas' perennialist thinking and the Pancasila Student Profile established by the government. The main focus of this research is to explain the Pancasila Student Profile which includes values ​​such as: faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation, independence, critical reasoning and creativity. This profile is relevant to the spiritual values ​​expressed by Thomas Aquinas in his perennialist educational philosophy. The application of these spiritual values ​​is implemented in the Project for Strengthening the Profile of Pancasila Students in schools in order to strengthen the spiritual values ​​that have existed since dozens of centuries ago. The spiritual values ​​that are explored are religious morals, personal morals, morals towards humans, morals towards nature and state morals. These five morals are in accordance with the philosophical view of perennialism from the perspective of Thomas Aquinas.